PENGARUH PENERIMAAN RETRIBUSI DAN PENETAPAN TARIF OBYEK WISATA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN GUNUNG KIDUL TAHUN 2013-2015 - Sunarto Sunarto; Reni Dyah Ayu Nur Fatimah (Jurnal Akuntansi, 2016)
The purpose of this research is to determine the effect Admission and Determination of Rates Levy Heritage simultaneously and partially on the level of revenue. The population in this research is a report on actual revenues levies, tariffs sights and Local Revenue 2013-2015 period. The sampling technique used purposive sampling technique. The data in this research will be tested using statistical test, classic assumption test, and analyzed using multiple regression analysis. The results showed that Levy Admission and Determination of Rates Heritage simultaneous positive effect on regional revenue. P-value was 0,000. This means shows that the p-value is smaller than a predetermined level of 5%. In t test, it was concluded that the Levies Revenue partially positive effect on regional revenue. Because it is known that p-value